2019
DOI: 10.9734/afsj/2019/v9i130003
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Extended-Spectrum Beta-Lactamase (ESBL)-Producing Bacteria in Salad Vegetables in Ondo City, Nigeria

Abstract: Aim:This study was carried out to determine the occurrence of extended-spectrum betalactamase (ESBL) producing bacteria in salad vegetables in Ondo City, Nigeria. Study Design: An experimental study design with randomized sampling. Place and Duration of the Study:The research was carried out in the Methodology: Samples of cucumber, carrot, green pea, green beans, sweet corn and cabbage were analysed on appropriate agar medium. Pure isolates were identified by biochemical tests and confirmation was done by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…It causes bacterial intestinal and extra-intestinal infections including septicaemia, diarrhoea, urinary tract infections, and neonatal meningitis in man and livestock ( 24 ). It is often linked with multiple antimicrobial resistances ( 25 ), and among bacteria isolated from animal foods, such as pigs, cattle, and poultry ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…It causes bacterial intestinal and extra-intestinal infections including septicaemia, diarrhoea, urinary tract infections, and neonatal meningitis in man and livestock ( 24 ). It is often linked with multiple antimicrobial resistances ( 25 ), and among bacteria isolated from animal foods, such as pigs, cattle, and poultry ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…The relatively weak activity of these antibiotics suggests that many of the resistant isolates could contain the enzyme βlactamase, deactivating the β-lactam rings of the βlactam antibiotics and cephalosporins. This is buttressed by the findings of Bello et al (2019) who reported the resistance profile of β-lactamaseproducing bacterial isolates from salad vegetables (Bello et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Occurrence of these resistant strains further suggests imminent danger of gastrointestinal disease outbreak from retailed tomato in most parts of southwest Nigeria. Poor post-harvest storage conditions of food materials, poor food handling practices, and unhygienic cooking habits in common street canteens and restaurants are gradually increasing resistant foodborne pathogens as well as other extended-spectrum beta-lactamases-producing strains in food materials in many communities [21], [56]. Clonal relatedness of highly resistant enteric Klebsiella aerogenes and Citrobacter freundii from Nigerian tomatoes with human, food, and milk products from other countries further indicate high genetic mobility and transfer from animal milk products, human contamination probably from fecal that could drive genetic reassortment leading to spread of phylo-diverse pathotypes [20], [57], [58], [59].…”
Section: Discussionmentioning
confidence: 99%
“…However, the incidence of foodborne disease is now becoming a public health issue considering the recent outbreaks of foodborne diseases in various countries due to consumption of contaminated raw fruits [15], [16], [17], [18]. The previous reports have implicated presence on pathogens on surfaces of fresh fruits and vegetables which includes Escherichia coli, Salmonella paratyphi typhi, Klebsiella pneumonia, Yersinia pestis, Shigella dysenteriae, and Listeria monocytogenes; however, there is still paucity of studies to determine the public health implication of consuming the contaminated tomatoes which are often used by many local food eateries in Nigeria [19], [20], [21], [22], [23]. There is need to determine bacteria contaminants in tomatoes and check their antimicrobial susceptibility to common content that may constitute risk to public health [24].…”
Section: Introductionmentioning
confidence: 99%